Workforce Inclusion and the Glass Cliff: Women’s Leadership Experience in Nigeria - Ginger-Eke, Onyekachi Enuma (Global journal of Business and Integral Security, 2026)
This paper draws on my doctoral research exploring the lived experiences of senior women leaders in Nigeria, particularly how they navigate the “glass cliff”—a phenomenon where women are appointed to senior leadership positions during periods of heightened risk—highlighting how gendered power structures and institutional inequities shape leadership trajectories. The study adopts a qualitative, critical theoretical approach, drawing on in-depth interviews with senior women leaders across public and corporate sectors. Thematic analysis was applied to capture lived experiences, leadership strategies, and institutional responses. Findings reveal that women leaders frequently face unstable mandates, limited structural support, and heightened scrutiny, yet deploy adaptive leadership, informal mentoring, and network-building to drive reform. These strategies challenge entrenched norms but remain constrained by systemic barriers. This research advances understanding of gendered leadership in high-stakes contexts and offers a framework for building equitable governance systems. Recommendations include reforming leadership appointment processes, embedding mentorship pipelines, and integrating gender equity into digital and green economy transition policies.